2014
DOI: 10.1016/j.tcs.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of confluence and ample sets in probabilistic and non-probabilistic branching time

Abstract: Confluence reduction and partial order reduction by means of ample sets are two different techniques for state space reduction in both traditional and probabilistic model checking. This paper provides an extensive comparison between these two methods, and answers the question how they relate in terms of reduction power when preserving branching time properties. We prove that, while both preserve the same properties, confluence reduction is strictly more powerful than partial order reduction: every reduction th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Hence, it would not even preserve Markovian divergence-insensitive branching bisimulation. We now improve on the definition to resolve this issue, introducing τ -loops in the reduced system for states having confluent divergence in the original system (inspired by the way [17] deals with divergences). This not only makes the theory work for MAs, it even yields preservation of divergence-sensitive branching bisimulation, and hence of minimal reachability probabilities.…”
Section: Confluence For Markov Automatamentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it would not even preserve Markovian divergence-insensitive branching bisimulation. We now improve on the definition to resolve this issue, introducing τ -loops in the reduced system for states having confluent divergence in the original system (inspired by the way [17] deals with divergences). This not only makes the theory work for MAs, it even yields preservation of divergence-sensitive branching bisimulation, and hence of minimal reachability probabilities.…”
Section: Confluence For Markov Automatamentioning
confidence: 99%
“…Also, several types of partial order reduction (POR) have been defined, both for nonprobabilistic [26,21,16] and probabilistic systems [11,4,3]. These techniques are based on ideas similar to confluence, and have been compared to confluence recently, both in a theoretical [17] and in a practical manner [18]. The results showed that branching-time POR is strictly subsumed by confluence, and that the additional advantages of confluence can be employed nicely in the context of statistical model checking.…”
Section: Introductionmentioning
confidence: 99%
“…POR was first generalised to the probabilistic domain preserving linear time properties [2,6], with a later extension to preserve branching time properties [1]. Confluence reduction was generalised in [8,14], preserving branching time properties.…”
Section: Introductionmentioning
confidence: 99%
“…Also, several types of partial order reduction (POR) have been defined, both for nonprobabilistic [26,21,16] and probabilistic systems [11,4,3]. These techniques are based on ideas similar to confluence, and have been compared to confluence recently, both in a theoretical [17] and in a practical manner [18]. The results showed that branching-time POR is strictly subsumed by confluence, and that the additional advantages of confluence can be employed nicely in the context of statistical model checking.…”
Section: Introductionmentioning
confidence: 99%
“…It is key to the way we detect confluence on MAPA specifications. -We now do preserve divergences and hence minimal reachability probabilities, incorporating a technique used earlier in [17].…”
Section: Introductionmentioning
confidence: 99%